Pengaruh Animasi Cerkak Terhadap Perkembangan Kemampuan Berbahasa Jawa Krama Anak Usia 5-6 Tahun - Wijayanti, Elysa; Wulandari, Rifa Suci; Mustikasari, Rizki (STKIP PGRI Ponorogo Press, 2024)
Javanese language needs to be developed from an early age, and as time goes by, the language is increasingly being abandoned. Early childhood is a golden period that is able to receive optimal stimulation. The storytelling method using animated media is an interesting learning medium for children, so stimulation will be easy to capture. The Javanese language skills of children at RAM Miftahussalam are still low, and the use of digital media is also still lacking. The aim of this research is to determine the effect of the Cerkak animation media on the Javanese language skills of children at RAM Miftahussalam. This research uses a quasi-experimental research design. The research subjects used by researchers were children aged 5–6 years, or group B, at RAM Miftahussalam Ponorogo. The research subjects used by researchers were children aged 5–6 years, or group B, at RAM Miftahussalam. The data analysis technique uses a quantitative method with a paired sample t-test on two groups of pretest and posttest data. Data collection techniques in this research used observation instruments and oral test sheets. The results of the research show that the cerkak animation has an influence on the Javanese language skills of young children at RAM Miftahussalam. From the output results of SPSS 25 data analysis, it shows that the significance value (2-tailed) of the Paired Difference column is 0.000<0.05, so it can be concluded that H0 is rejected and Ha is accepted. Based on the paired samples t-test table, the tcount results were 23.110 and the ttable was 1.697. After treatment, tcount is greater than ttable, namely 23.110>1.679. Based on the decision-making criteria, it can be concluded that H0 is rejected and Ha is accepted, which means that there is a significant difference between before and after treatment using cerkak animation on the Javanese language skills of young children.